2017
DOI: 10.1016/j.jclinepi.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Further exploration of dissemination bias in qualitative research required to facilitate assessment within qualitative evidence syntheses

Abstract: Further exploration of dissemination bias in qualitative research is needed, including the extent of non-dissemination and related dissemination bias, and how to assess dissemination bias within qualitative evidence syntheses. We also need to consider the mechanisms through which dissemination bias in qualitative research could occur to explore approaches for reducing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…When findings from qualitative research are not spread and, consequently, are not accessible, bias may occur that could, in turn, threaten the quality of the qualitative counterpart of systematic reviewing: the qualitative evidence synthesis (Booth 2017). Dissemination bias in qualitative research has different causes than in quantitative research, but also negative consequences for scientific research and specifically, for the practice of systematic reviews (Toews et al 2017). When your qualitative study is preregistered, interested researchers can nevertheless find your study and ask you to take it out of the file-drawer, which could in turn ensure that qualitative evidence syntheses are more reflective and up to date.…”
Section: Practical Usefulness Of Preregistrations In Qualitative Resementioning
confidence: 99%
“…When findings from qualitative research are not spread and, consequently, are not accessible, bias may occur that could, in turn, threaten the quality of the qualitative counterpart of systematic reviewing: the qualitative evidence synthesis (Booth 2017). Dissemination bias in qualitative research has different causes than in quantitative research, but also negative consequences for scientific research and specifically, for the practice of systematic reviews (Toews et al 2017). When your qualitative study is preregistered, interested researchers can nevertheless find your study and ask you to take it out of the file-drawer, which could in turn ensure that qualitative evidence syntheses are more reflective and up to date.…”
Section: Practical Usefulness Of Preregistrations In Qualitative Resementioning
confidence: 99%
“…The aims of this paper are to discuss a definition of dissemination bias in qualitative research and consider how and to what extent it might occur, to explain why dissemination bias may be important in relation to the process and findings of qualitative evidence syntheses, to discuss how dissemination bias might impact on assessments of confidence in findings from qualitative evidence syntheses and to outline an agenda for future research. A complementary paper takes a broader look at dissemination bias in qualitative research and potential lessons from available evidence in the quantitative research arena to inform an understanding of the causes and consequences of dissemination bias in qualitative research [ 1 ]. Key definitions for the series are provided in Additional file 1 .…”
Section: Aimsmentioning
confidence: 99%
“…The survey findings suggest that the proportion of unpublished qualitative studies and individual findings is substantial and comparable to the extent of non-dissemination of studies using quantitative methods. Considerable further research is needed on both the extent of dissemination bias in qualitative research, including partial reporting of research findings, and the factors that affect this––we discuss this research agenda in more detail below and in a complementary paper [ 1 ].…”
Section: What Is the Extent Of Dissemination Bias In Qualitative Resementioning
confidence: 99%
“…Nevertheless, all studies reported that data saturation was achieved. We cannot rule out dissemination bias [ 46 ]. In all, 4 of 19 studies included were from the same group of authors.…”
Section: Discussionmentioning
confidence: 99%